An International Survey to Understand Infection Control Practices for Spinal Cord Stimulation. Issue 1 (22nd October 2015) - Provenzano, David A.; Deer, Timothy; Luginbuhl Phelps, Amy; Drennen, Zachary C.; Thomson, Simon; Hayek, Salim M.; Narouze, Samer; Rana, Maunak V.; Watson, Tyler W.; Buvanendran, Asokumar
Abstract : Objectives: Surgical site infections (SSIs) are associated with significant healthcare costs and morbidity. Limited research exists specific to the prevention of spinal cord stimulation (SCS) SSIs. The objectives of this international survey were to examine current infection control practices for SCS trials and implants and to compare reported responses with evidence‐based recommendations. Materials and Methods: A 33‐question survey was developed based on an extensive literature review for infection control policies. The survey was hosted on the Internet. Dispersion of the survey occurred through professional associations and device manufacturers. Responses to 15 questions directly related to defined CDC, NICE, and SCIP evidence‐based infection control practice recommendations were classified as either compliant or noncompliant. The survey was open for 20 days. Responses also were grouped and analyzed based on geographic location, practice location, and procedural volumes. Results: Five hundred six physicians responded to the survey. Compliance rates for CDC, NICE, SCIP infection control practice recommendations were low with only four of the 15 questions having compliance rates ≥80%. Areas associated with high levels of noncompliance included weight‐based antibiotic dosing, hair removal strategies, double gloving, surgical dressing, skin antiseptic agent selection, and postoperative continuation of antibiotics. Geographic and practice type variations existed for particular infection control practices. Procedural volume influenced operative implant times with low physician procedural volumes associated with extended operative times. Conclusions: The survey provided significant insight into current practices and will assist in the development of specific SCS infection control policies. Based on the survey, further education is warranted on infection control strategies for physicians performing spinal cord stimulator trials and implants.